Effect of the phase of the season and contextual variables on match running performance in Spanish LaLiga football teams - González-Rodenas, J.; Ferrandis, J.; Moreno-Pérez, V.; LópezDel Campo, R.; Resta, R.; Del Coso, J. (Biology of Sport, 2024)
This study aimed to examine the intra-season variation and the effects of contextual variables on total distance (TD), high-intensity running distance (HIRD) and high-speed distance (HSD) covered by Spanish football teams. The sample included 20 professional teams that competed in the Spanish LaLiga during the 2021-2022 season. Data were recorded using the TRACAB (ChyronHego, New York, USA) multicamera computerized optical tracking system. Multilevel linear mixed models were used to examine the effects of five contextual variables (1: phase of the season in six periods, 2: match location, 3: opponent ranking, 4: team ranking and 5: congested schedule) on TD, HIRD and HSD. Teams increased the running performance from period 1 to 5 of the season in TD (+2.2%; P < 0.05) and from period 1 to 4 in HIRD (+7.2%; P < 0.05), while a declining effect was found in period 6 for both TD (-1.2%; P < 0.05) and HIRD (-5.8%; P < 0.05). More HIRD (+1.5) and HSD (+5.3) were covered at home (P < 0.05), and more TD and HIRD were covered when playing against opponents ranked in the first (+2.4% and +5.3%, respectively; P < 0.05) and second quartile (+1.2% and +5.0%, respectively; P < 0.05), compared to teams from the fourth quartile. Football coaches and fitness specialists should note that running performance of Spanish teams increased throughout the season, but it declined during the last matches of the competition. Additionally, home matches and highranked opponents elicited higher running demands.